2014
DOI: 10.4014/jmb.1310.10121
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Novel ��-Amylase from a Fecal Microbial Metagenome

Abstract: To isolate novel and useful microbial enzymes from uncultured gastrointestinal microorganisms, a fecal microbial metagenomic library of the pygmy loris was constructed. The library was screened for amylolytic activity, and 8 of 50,000 recombinant clones showed amylolytic activity. Subcloning and sequence analysis of a positive clone led to the identification a novel gene (amyPL) coding for α-amylase. AmyPL was expressed in Escherichia coli BL21 (DE3) and the purified AmyPL was enzymatically characterized. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…3). On the contrary, Xu et al (2014) reported that the optimum temperature for the best amylase activity of purified AmyPL was 50∞C. Thus, it can be assumed that mutation might improve the activity by altering the dynamic properties of residues in the active site of the enzyme.…”
Section: Characterization Of Purified a A A A A-amylase From Wild Andmentioning
confidence: 89%
“…3). On the contrary, Xu et al (2014) reported that the optimum temperature for the best amylase activity of purified AmyPL was 50∞C. Thus, it can be assumed that mutation might improve the activity by altering the dynamic properties of residues in the active site of the enzyme.…”
Section: Characterization Of Purified a A A A A-amylase From Wild Andmentioning
confidence: 89%
“…Its temperature and pH optima were 10–15°C and pH 8–9. α-Amylases have also been reported from metagenomic libraries from pygmy loris ( Nycticebus pygmaeus ) and cow dung (Xu et al, 2014 ; Sharma et al, 2015 ).…”
Section: Diversity Of α-Amylasesmentioning
confidence: 98%
“…The animal is believed to be domesticated for as long as 8000 years, during which common salt was exclusively provided to the animal by local farmers as an additional feed ( Das et al, 2011 ). This study screened salt-tolerant clones from the constructed fecal metagenomic library of N. pygmaeus and B. frontalis ( Xu et al, 2014 ; Dong et al, 2016 ). We analyzed potential salt-tolerant genes and enzymes through high-throughput sequencing and bioinformatics technology.…”
Section: Introductionmentioning
confidence: 99%